Pengaruh Nisbah Kelamin Perkawinan Terhadap Litter Size dan Jumlah Anak Perkandang Perkawinan Tikus Putih Wistar - Taofik, Ahmad; Depison, Depison (Fakultas Peternakan Universitas Jambi, 2008)
This research was conducted to know the influence of sex ratio parental on pregnant females, litter size and output per breed of white wistar rat. Experiment started on January 1st – March 10th, 2008. This experiment sample was taken from PAU Institute Teknology Bandung and it done at Garden of Botany of Faculty of Mathematics and Natural Sciences of University of Education Indonesia. As many 128 white wistar rat consisted of 112 females mating old (virgin) with body weight 162-235 gram and 16 males mating old with body weight 275-325 gram placed randomly into cage 60 cm x 40 cm x 25 cm. This research was used experiment methode with Completely Randomized Design (CRD). The treatment, were R1 = 1 : 4 (1 male and 4 females), R2 = 1 : 6 (1 male and 6 females), R3 = 1 : 8 (1 male and 8 females) dan R4= 1 : 10 (1 male and 10 females). The placement was according to treatment group and each treatment repeated four times. Males and females oestrus kept together until five days, account the pregnant females, litter size, and output per breed of white wistar rat. Analysis of Variance was used to analyse the data. The result of this research indicated that sex ratio not significantly (P > 0,05) on pregnant females, litter size and output per breed of white wistar rat.